1996
DOI: 10.1111/j.1752-7325.1996.tb02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Amount and Type of Dental Services Received by Older Adults in Four Municipalities in Ontario, Canada

Abstract: Both dentate and edentulous visitors received over two hours of care per person per year. Dental care patterns were influenced by dental status, area of residence, and visiting behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
15
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
(4 reference statements)
4
15
1
Order By: Relevance
“…This study confirms an earlier study that found considerable geographic variation in the volume of dental services provided to older Ontario adults (15). In the earlier study data on dental services 280 were collected for the 2-year period prior to enrolment in a longitudinal oral health survey.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms an earlier study that found considerable geographic variation in the volume of dental services provided to older Ontario adults (15). In the earlier study data on dental services 280 were collected for the 2-year period prior to enrolment in a longitudinal oral health survey.…”
Section: Discussionsupporting
confidence: 89%
“…This interest arose out of the preliminary study by Leake and colleagues (15) which found a two-fold difference in the amount of dental care received over 2 years by older adults living in the cities of Toronto and North York, two metropolitan communities, and older adults living in Simcoe County and Sudbury, which are rural and northern industrial communities approximately 100 and 400 km north of the metropolitan area. How much variation is there in the volume and pattern of care they receive and what explains that variation?…”
mentioning
confidence: 99%
“…Conservative treatment dominated in the most recent dental treatment course of our seniors, indicating efforts to retain their teeth. Four out of five of our seniors reported having received filling therapy, which corresponds to dentists’ reports on treatments they give their elderly patients 22,26,27 . Population studies, on the contrary, report clearly lower rates for filling therapy: 25% in the UK, 57% in Finland and 32% in Lithuania 8,10,14 .…”
Section: Discussionsupporting
confidence: 70%
“…Our results for elderly patients are in line with those of a previous Lithuanian report 8 revealing a serious under‐use of preventive measures compared with seniors in industrialised countries: 54% in the UK 10 and 68% in Finland 14 . Dentists’ reports on seniors in Canada and Australia also indicate very high rates of preventive treatments 22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Where comparisons to other studies can be made, the percentage of persons in the FDCS who used services is similar for some service categories, but substantively different for other categories. For example, a study (34) (of Canadians aged 50‐years or older) observed that among dentate participants, 44% received a silver filling and 47% received a tooth‐colored filling (compared to 32% in the FDCS which pooled all fillings into one category), 18% received a crown and 4% received a fixed bridge (compared to 29% in the FDCS which pooled crowns and bridges into one category), 11% received an endodontic service (compared to 7% in the FDCS), and 15% received a denture service (compared to 13% in the FDCS) in a 2‐year period. In a 2‐year pilot dental care program for low‐income senior citizens, which included both edentulous and dentate participants, Yellowitz et al.…”
Section: Discussionmentioning
confidence: 99%